Yield, plasticity, stability and homeostasis of spring barley cultivars in the Non-Black Earth Region - L. M. Eroshenko; M. M. Romakhin; N. A. Eroshenko; I. A. Dedushev; V. V. Romakhina; M. A. Boldyrev (Труды по прикладной ботанике, генетике и селекции)
Background. The expansion of agrometeorological factors negatively affecting the productivity of spring barley has oriented plant breeders towards developing adaptable forms capable of realizing their genetic potential for higher yield under unfavorable conditions. Applying several methods of statistical data analysis helps to perform a more accurate assessment of the material differentiated according to its adaptability indicators. The objective of this study was to assess the adaptability of spring barley cultivars on the basis of their yield, plasticity, stability and homeostasis.Materials and methods. The resulting data were obtained for ten spring barley cultivars developed at Nemchinovka FRC.Results. High yield potential of more than 8.5 t/ha was disclosed in barley cultivars ‘Yaromir’, ‘Nur’, ‘Nadezhny’, ‘Sudar’, ‘Zlatoyar’ and ‘Znatny’. Cvs. ‘Luboyar’, ‘Nadezhny’ and ‘Rafael’ showed the highest adaptability to the worst growing conditions (4.65–5.04 t/ha) as well as high adaptive and compensatory ability. Cvs. ‘Sudar’, ‘Nur’ and ‘Zlatoyar’ were identified for high environmental plasticity (Cvi = 24.1–25.9%; bi = 1.02–1.16; σ = 1.52–1.59), while ‘Lyuboyar’, ‘Znatny’ and ‘Vladimir’ for their stability parameters (S2di = 0.05–0.19; σ2CACi = 1.60–1.78; σ2(G×E)gi = 0.05–0.15). The highest values of homeostasis (BVGi = 3.45– 3.53; CSLi = 138.7–139.4; Homi = 9.02–9.85) were registered for cvs. ‘Rafael’ and ‘Lyuboyar’. The calculated rating of the tested cultivars identified ‘Nadezhny’ as the best in productivity, while ‘Zlatoyar’ was the best in environmental plasticity. The highest levels of stability and homeostasis were recorded for cvs. ‘Rafael’ and ‘Lyuboyar’.Conclusion. Comprehensive assessment of productivity and adaptability indicators in the tested spring barley cultivars showed that ‘Lyuboyar’, ‘Nadezhny’, ‘Zlatoyar’ and ‘Rafael’ were the best under the conditions of the Non-Black Earth Region.